MEMAHAMI PENGALAMAN PENDAMPINGAN KOMUNIKASI ORANG TUA TUNGGAL TERHADAP ANAK PENYINTAS PERUNDUNGAN - Riesma Laylinisa; Hapsari Dwiningtyas Sulistyani; Primada Qurrota Ayun (Interaksi Online, 2022)
In reality, there are various forms of family. Unfortunately, society has not been able to appreciate the diversity of family forms. In fact, children raised by single parents, such as single mothers, are bullied due to their parents' divorce. This research aims to understand the experience of single-parent communication assistance to child survivors of bullying. This research uses a descriptive phenomenological approach, with four informants participating in the study. The four informants are single mothers and have children who have experienced bullying due to their parents' divorce. The theory developed in this research is a theory that explains dialogic communication, namely Dialogic Communication Theory, and a theory that explains relationship maintenance or Relationship Maintenance Theory. Based on the findings in the study, Speech Act Theory was added. Through this research, we can understand that communication assistance by single mothers is carried out with various efforts, not only by words but also by taking concrete actions, such as maintaining emotions when interacting with children, listening to children carefully, providing advice and direction, utilizing applications chat, as well as the role of other family members in giving attention. Single mothers also offer communication assistance by strengthening their children and not becoming authoritarian parents. Single mothers provide confidence to their children to grow selfconfidence. Communication assistance makes the child grow up more confident, independent, not easily giving up, and able to better understand the situation. Thus, the communication assistance carried out by single mothers is an integration of giving attention, strengthening, and trusting.